2018
DOI: 10.1177/0886260518787815
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Culture on Healthy Relationship Formation and Teen Dating Violence: A Qualitative Analysis of South Asian Female Youth Residing in the United States

Abstract: Teen dating violence (TDV) has well-documented detrimental health effects. Scant research has examined the perspectives of ethnically diverse youth about the impact of culture on TDV. We sought to explore the intersection between culture and TDV specifically for South Asian youth residing in the United States. We conducted semi-structured interviews with South Asian youth aged 16 to 21 years. Interviews included three aims: (a) exploring participants' perspectives on TDV and healthy relationships within the So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
(52 reference statements)
2
15
0
Order By: Relevance
“…Further, the young Thai women had clear cut views on what was expected behaviour of a good and bad girl but expressed no such expectations of young men (Thongpriwan & McElmurry, 2009). Similarly, an American study of South-Asian origin young women revealed that young women were judged harshly by community members for being involved in dating relationships as dating is stigmatised, whereas this was not necessarily the case with young men (Ragavan et al, 2018).…”
Section: Dating Is Genderedmentioning
confidence: 98%
See 2 more Smart Citations
“…Further, the young Thai women had clear cut views on what was expected behaviour of a good and bad girl but expressed no such expectations of young men (Thongpriwan & McElmurry, 2009). Similarly, an American study of South-Asian origin young women revealed that young women were judged harshly by community members for being involved in dating relationships as dating is stigmatised, whereas this was not necessarily the case with young men (Ragavan et al, 2018).…”
Section: Dating Is Genderedmentioning
confidence: 98%
“…The rules by which young women abide within dating relationships are gendered and there is social pressure to conform to these gendered ideals (Chung, 2007;Luft, Jenkins, & Cameron, 2012;Noel et al, 2016). Young men tend to adopt more dominant roles within heterosexual dating relationships while young women adopt more passive roles, in keeping with traditional patriarchal social structures (Banister & Jakubee, 2004;Banister, Jakubec, & Stein, 2003;Chung, 2007;Ismail et al, 2007;Luft et al, 2012;Noel et al, 2016;Ragavan, Syed-Swift, Elwy, Fikre, & Bair-Merritt, 2018). Young women provided examples of endorsing heterosexual norms informed by patriarchal social structures including prioritising the relationship, taking a more submissive role within the relationship, being sexual gatekeepers of the relationship and taking key responsibility for the relationship's well-being (Banister & Jakubee, 2004;Chung, 2007;Ismail et al, 2007;Jackson, 2001;Jeffrey & Barata, 2017;Luft et al, 2012), and this was not different to young women who identified with non-Western cultures (Haglund, Belknap, & Garcia, 2012;Ragavan et al, 2018;Thongpriwan & McElmurry, 2009).…”
Section: Dating Is Genderedmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased risk of DV victimization has been also reported by female and male adolescents who have been exposed to other forms of violence (childhood exposure or witnessing different forms of violence, bullying), poor quality friendships and family relationships and the presence of harmful attitudes such as sexism, machismo, or violence acceptability [7][8][9][10]. Conversely, a higher sense of attachment to school and teachers seems to be associated to a lower likelihood of both DV victimization and perpetration [11].…”
Section: Introductionmentioning
confidence: 97%
“…An increased risk of DV victimization has been also reported by female and male adolescents who have been exposed to other forms of violence (childhood exposure or witnessing different forms of violence, bullying), poor quality friendships and family relationships, and the presence of harmful attitudes such as sexism, machismo, or violence acceptability [ 7 10 ]. Conversely, a higher sense of attachment to school and teachers seems to be associated with a lower likelihood of both DV victimization and perpetration [ 11 ].…”
Section: Introductionmentioning
confidence: 99%